2014
DOI: 10.1051/e3sconf/20140301004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Occupants’ Satisfaction for Safety Performance Assessment in Low Cost Housing

Abstract: Abstract. The delivery performance of the low cost housing is questioned since the occupants are prone towards safety hazards in the housing complex, such as structural instability and falling building fragments. Without defining the occupants' requirements for the development of low cost housing, the prevailing safety factors are hard to be determined. This paper explores the rationale of safety performance assessment in the low cost housing by considering the occupants' participation to achieve a better safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Much past research focused on the poor quality of completed high-rise low-cost housing units. Husin et al (2014) reported that in their survey of 380 low-cost residents, the respondents were most concerned about the safety performance of various elements of the house: metal grille; the building structure; roof and plumbing system; tiling works; wall finishes; internal ventilation, etc. In another survey conducted with 510 low-cost residents (though only 35% of the respondents were owner-occupiers), Wahi et al (2018) identified four areas of quality dissatisfaction: house workmanship, plumbing system, house design and material quality.…”
Section: The Physical Characteristicsmentioning
confidence: 99%
“…Much past research focused on the poor quality of completed high-rise low-cost housing units. Husin et al (2014) reported that in their survey of 380 low-cost residents, the respondents were most concerned about the safety performance of various elements of the house: metal grille; the building structure; roof and plumbing system; tiling works; wall finishes; internal ventilation, etc. In another survey conducted with 510 low-cost residents (though only 35% of the respondents were owner-occupiers), Wahi et al (2018) identified four areas of quality dissatisfaction: house workmanship, plumbing system, house design and material quality.…”
Section: The Physical Characteristicsmentioning
confidence: 99%